CEI (Production Engineer, 1976)
BACKGROUND: Currently the role of dengue virus (DENV) specific T cell responses in disease pathogenesis and protection are not well understood, including potential differences in those who have obesity. We sought to investigate the functionality and phenotype of T cells in patients with acute dengue fever (DF) or dengue haemorrhagic fever (DHF). METHODS: T cell function was assessed in paired samples (first sample on ≤4 days and second 5-6 since onset of illness) in patients with DF (n=50) and DHF (n=12), using 109 peptides representing CD8+ epitopes and 90 peptides targeting CD4+ T cell epitopes. Phenotypic analysis was in DF (n=21) and DHF patients (n=21), recruited between days 6-8 since onset of illness, by multicolor flow cytometry. RESULTS: The frequency of ex vivo IFNγ ELISpot responses to both the CD4+ and CD8+ peptides pools significantly increased from the first (F) to second time (S) point in patients with DF (p<0.0001) but not with DHF. The frequency of ex vivo IFNγ ELISpot responses to CD4+ (p=0.001) and CD8+ peptides pools (p=0.0002) also significantly increased from the F to S in lean patients but not in obese patients. Cutaneous lymphocyte associated antigen (CLA) expression was significantly higher in the CD8+ T cell subset in patients with DF and DHF compared to HC and these differences were most significant in CD8+CD45RA- T cells. CD8+CD45RA-CLA+ T cells consisted of >50% of the T cells in 9/21 patients with DHF, with 92.7% expressing CD38. CLA expression was highest in the CD8+CD45RA- of obese individuals, which was significantly higher compared to lean individuals (p=0.01). CD27 and CD127 were both significantly downregulated in patients with DHF compared to DF, with ICOS expression being significantly higher in CD8+ T cells in DHF. DISCUSSION: Patients with DHF and obese individuals had impaired T cell functionality compared to patients with DF and lean individuals, with an expansion of activated, skin-homing CD8+ T cells exhibiting downregulation of CD27 and CD127. Our data suggest a contributory role of dysfunctional skin-homing T cells in disease pathogenesis, meriting further investigation.